TAXPAYER PERCEPTION RELATED TO LOVE OF MONEY, MACHIAVELLIAN, AND EQUITY SENSITIVITY ON TAX EVASION ETHICS - Esther Dwitia; Masripah Masripah; Ni Putu Eka Widiastuti (Jurnal Akuntansi dan Perpajakan Jayakarta, 2020)
Cases of tax evasion in Indonesia have occurred a lot, giving rise to different perceptions on everyone. This study aims to determine the effect of love of money, machiavellian, and equity sensitivity on tax evasion ethics of taxpayers. The population of this research is individual taxpayers who are obliged to tax return and are registered in KPP Pratama in Jakarta, Bogor, Tangerang and Bekasi (Jabotabek) areas. The sample was collected by snowball sampling method. The data used in this study are primary data by using questionnaire with 100 respondents as individual taxpayers. Data analysis was performed using Microsoft Excel 2013 and SmartPLS 3.0. The results of this study showed that (1) love of money has an effect on ethics of tax evasion. (2) machiavellian has no effect on ethics of tax evasion. (3) equity sensitivity has no effect on the ethics of tax evasion. Recomendation for further researchers to be able to add independent variables such as cultural factors, intelligence levels and expand population areas to produce better research. Keywords: Love of Money, Machiavellian, Equity Sensitivity, Tax Evasion Ethics